Civil control and - (:unkn) unknown (My University, 2016)
The process of reforming the Judicial Branch opens up extraordinary opportunities for capturing the design of key institutions in the system. Many of the reforms that have been carried out in Latin America havefocused on conditions for selecting, appointing and impeaching judges. In order to address these issuesvarious reforms consider the creation of Judiciary Councils (Consejos de la Magistratura). This article uses apractical case to demonstrate why it is necessary to exercise strict control over the design of and eventualchanges to the regulations that define the internal functioning of the Judiciary Councils above and beyondthe Constitution and the regulatory law that created the institution and put it into operation.